Multisensory Method Training in Craft Arts (Fabric Marbling) for Students with Hearing Impairments (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2026)
Students with deaf disabilities often have difficulty understanding verbal instruction, but have significant advantages in visual and motor aspects. This service activity aims to apply multisensory methods through Suminagashi craft art training (cloth marbling) to improve students' fine motor skills and creativity at SLB B Yakut Purwokerto. The implementation method uses a descriptive qualitative approach with a "see-learn-do" strategy involving 20 high school students. The learning process integrates visual stimulation through structured demonstrations and tactile stimulation through the exploration of material textures. The results of the activity showed that the multisensory approach was effective in bridging the barriers of deaf students with disabilities in communicating due to hearing limitations. Students demonstrate a high level of visual focus and are able to replicate marble motif making techniques with precision without relying on complex verbal explanations. The combination of cue instructions and direct touch experiences has been proven to minimize miscommunication and improve understanding of abstract concepts of the material. This activity recommends the use of visual-tactile strategies as an adaptive inclusive learning method to support the vocational independence of deaf people.